International Year of Planet Earth 6. Biosignatures: Interpreting Evidence of the Origins and Diversity of Life - Slater, G. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2009)
SUMMARY Biosignatures are molecular, mineral or isotopic patterns that can be unambiguously interpreted as evidence of life and so provide the means for us to address our most fundamental questions about the origins and evolution of life. Biosignatures of microbial life are especially important to our understanding of early Earth history, and can be recorded in magnetic mineral traces, various carbon compounds, and stable isotope ratios of many elements. These signatures, preserved in the geologic record, represent the primary means by which we gain insight into the early history of life on Earth, including the timing of the origins of life and major interactions of life with its environment, such as the oxidation of the Earth’s atmosphere. In addition, microbial biosignatures are also considered one of the most likely targets in the search for life beyond Earth. However, identifying and interpreting geochemical biosignatures of microbial life is challenging and involves careful differentiation between signatures of biological processes and those of abiological processes. Canada is playing an important role in biosig-nature research, both through the geologic record of life preserved in our ancient rocks, and through many examples of microbial life in extreme environments. The latter provide the modern understanding required to interpret the biosignature record from early Earth and perhaps one day from another planet.